1995
DOI: 10.1021/j100030a001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of effective vibrational-translational energy exchange in collisions of vibrationally excited OH with O2 on the model potential energy surface. Can the relaxation of OH(v) be one-quantum for low and multiquantum for high v?

Abstract: The collision of OH with the oxygen molecule is studied by the trajectory simulation technique on the model potential energy surface of OH + 0 2 -0 3 + H chemical reaction. Although the reaction channel is closed, we aim to demonstrate that the L-shape of the OH + 0 2 valley leads to the effective coupling of OH(v) vibration with the relative motion of collisional partners and therefore explains the high value of the vibrational relaxation rate constant observed experimentally. The characteristic feature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 6 publications
5
35
0
Order By: Relevance
“…For example, the reaction leads to OH in vibrationally excited states with quantum numbers up to V′ ) 9. [2][3][4][5][6][7][8][9][10][11][12][13] In turn, photodissociation of ozone within the Hartley band yields vibrationally excited molecular oxygen with a distribution peaking in the vicinity of V′′ ) 14 and V′′ ) 27 14 according to the reaction Recently, another bimodal distribution has been observed in the photodissociation of ozone at 266 nm with peaks near V′′ ) 9 and V′′ ) 5. 15 An additional source of vibrationally excited oxygen molecules in the stratosphere is the reaction 16 with O 2 populating vibrationally excited levels up to V′′ ) 13.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the reaction leads to OH in vibrationally excited states with quantum numbers up to V′ ) 9. [2][3][4][5][6][7][8][9][10][11][12][13] In turn, photodissociation of ozone within the Hartley band yields vibrationally excited molecular oxygen with a distribution peaking in the vicinity of V′′ ) 14 and V′′ ) 27 14 according to the reaction Recently, another bimodal distribution has been observed in the photodissociation of ozone at 266 nm with peaks near V′′ ) 9 and V′′ ) 5. 15 An additional source of vibrationally excited oxygen molecules in the stratosphere is the reaction 16 with O 2 populating vibrationally excited levels up to V′′ ) 13.…”
Section: Introductionmentioning
confidence: 99%
“…reaction, the source of vibrationally excited hydroxyl radicals ahose einission spectrum is related to night-sky afterglow (3)(4)(5)(6)(7)(8)(9). Despite its relevance to atmospheric chemistry and its intrinsic fundarnental interest, H 0 3 has not been experimentally detected to date, and it has remained open whether it can survive dissociatioil into 0, and OH.…”
mentioning
confidence: 99%
“…Characterization of HO, as an intermediate. rather than as a fleeting HOi'O, con~plex or a transition state, has a direct bearing on atmospheric chemistry, in particular concerning its role in night-sky afterglo\\, and regarding the accurate kinetic modeling of the H + 0, reaction and the collisional quenching of vibrationally excited hydroxyl radicals by O,, two processes of current interest (7,24), owing to their i~nportance in at~nospheric chemistry. …”
mentioning
confidence: 99%
“…We have reported a QCT study of the reaction OHv 0 3 9 O 3 using a recently published DMBE potential energy surface for ground state HO 4 . The calculations have shown that the title reaction may occur both via capture-type and barrier-type mechanisms, depending on the reactant initial conditions, especially the degree of OH vibrational excitation.…”
Section: Discussionmentioning
confidence: 99%
“…The Letter is organized as follows. Section 2 gives a brief survey of the HO 4 2 A DMBE potential energy surface, while the computational method is described in Section 3. The dynamics results are presented and discussed in Section 4, and the major conclusions in Section 5.…”
Section: May 2001mentioning
confidence: 99%